Sino-Ghana bilateral relations and Chinese migrants' illegal gold mining in Ghana. Issue 3 (2nd September 2019) - Debrah, Emmanuel; Asante, Richard
ABSTRACT: This article examines the participation of some Chinese migrants in illegal gold mining (known as galamsey) in Ghana, and how the Government's policy to address the issue created diplomatic tension between China and Ghana. Drawing on primary data from in-depth, face-to-face interviews with 250 respondents and supplementary information from archival sources and personal observation, the study found that small-scale gold mining is an area legally reserved for Ghanaian indigenes, who faced stern competition from some Chinese migrants' miners. Their ability to mobilize resources and machinery to execute galamsey virtually displaced the indigenes from their source of livelihood and caused environmental catastrophes. The Ghana Government's policy response to the Chinese migrants' galamsey, which led to arrests, sentencing and deportations of some Chinese miners, angered Beijing and fractured Ghana–China diplomatic ties. But the dispute could not collapse the entrenched bilateral relations between the two nations because the calculated mutual benefit derived from the relations was thought to be higher than the Chinese galamsey issue. Policy reforms which legally integrate Chinese migrants' miners into the small-scale mining sector would stop galamsey and strengthen Sino-Ghana relations.